Disability evaluation after latissimus dorsi muscle transfer in breast reconstruction using DASH score - Sanchez, Jazmin V.; Guerrero, Rene R.; Rubio, Karla F. G. G.; Mancilla, Noe I. G.; Piña, Raymundo T. (International Journal of Research in Medical Sciences, 2024)
Background: Breast reconstruction with latissimus dorsi muscle transfer is one of the most frequent procedures at our hospital. The objective is to evaluate if there is any functional impairment after the surgery with a potential impact of patient´s daily life. Methods: Functional morbidity was analyzed applying the disabilities of the arm, shoulder and hand (DASH) questionnaire and shoulder range of motion with goniometer in 42 patients whose breast reconstruction was between 2016 and 2022 at our hospital. We collected data using Microsoft excel V16.47.1 and analyzed data with statistical package for the social sciences (SPSS) software, v23.0. Results: There was statistically significant difference for disability/symptom DASH score in cases of bilateral reconstruction and for cases undergoing a procedure on the right side versus left side. Conclusions: In patients with bilateral breast reconstruction, we found a greater DASH score in dysfunction and symptoms which associates with poor quality of life, as well as when the flap is on the contralateral extremity of the hand dominance; in those cases, there are other reconstructive procedures that provide greater safety and less disability to the patient. For evaluating extension, we need more prospective and comparative studies with strict follow up of the patients and same series of rehabilitation.